AMELIORATIVE EFFECT OF ASTAXANTHIN ON ISCHEMIA-REPERFUSION INJURY OF SKELETAL MUSCLES - A. Uyar; H. T. Akkoyun; A. Ş. Bengu; M. B. Akkoyun; Ö. F. Keleş; T. Atçali; Ş. Melek; T. Yaman (Journal of Animal and Plant Sciences, 2022)
This experimental study aimed to investigate the ameliorative effect of astaxanthin (AST) on the prevention of skeletal muscle injury resulting from lower extremity ischemia/reperfusion (I/R). Twenty-eight (250-300g) male Wistar albino rats were divided into 4 groups as Control, I/R, I/R+AST and AST. In the control group, only anesthesia was induced for 2 h without I/R. In the I/R group, 2 h of reperfusion was facilitated following ischemia under anesthesia. For the I/R+AST group, 7 days prior to ischemia, 125 mg/kg AST was given through a gavage, and 2 h of ischemia and 2 h of reperfusion were facilitated under anesthesia. At the end of the study, blood and gastrocnemius muscle tissue samples were taken for biochemical, histopathological and immunohistochemical examinations. Compared to the control group, there were increased Malondialdehyde (MDA) levels and decreased Superoxide dismutase(SOD) and Catalase (CAT) enzyme activities in the I/R group (p˂0.001). Degeneration, necrosis, inflammation, loss of striation, interfibrillar and interfascicular edema were seen in the histopathological examination of the skeletal muscles in the I/R group. These histopathological findings were minimal in the I/R+AST group. In the immunohistochemical examination of muscle tissue with the GPx1 primary antibody, a mild degree of GPx1 reactivity was observed in the I/R group, and a moderate degree of GPx1 reactivity was seen in the I/R+AST group. As a result, the strong ameliorative effect of AST on ischemia-reperfusion injury and its complications on skeletal muscles was demonstrated by biochemical, histopathological and immunohistochemical examinations.
Keywords: Ischemia-reperfusion; Muscle; Astaxanthin; MDA; SOD; CAT; Histopathology